Islam in Southeast Asia - Hussin Mutalib, 1949- (Book collections on Project MUSE., 2008)
Islam is a major religion in Southeast Asia, with Indonesian Muslims comprising the largest Muslim population in the world. Events and developments since 11 September 2001 have added greater attention to Islam and its adherents in this part of the world. This general survey of Islam in Southeast Asia is intended to inform, explain and update readers about the more significant aspects of Islam in Southeast Asia, then and now. These include the following: the geographical origins and sources by which the faith spread in this region; the social, economic and political profiles of the Muslim communities; relations between Muslims and non-Muslims and between Muslims and the State; the strands and trends that shapes the role of Islam and the Muslims in the national body politic; and the challenges confronting Muslims in confronting the vicissitudes of their lives in this era of rapid change, characterized by modernization, capitalism, secularization and globalization. The discussion will begin with an overview of the broad picture of Islam and the Muslims in the region as a whole, covering both Muslim-majority and Muslim-minority countries. This will be followed by case-study analysis of Islam and the Muslims in individual countries: Indonesia, Malaysia, Brunei, Singapore, Thailand, Philippines, Myanmar, Vietnam, Cambodia and Laos. Given the difficulty of writing on such a complex and contentious topic, this book attempts to present the subject matter in a manner that is sufficiently objective to scholars and yet simple and accessible enough to be readily understood by ordinary readers. -- publisher.